2002
DOI: 10.1002/cncr.10390
|View full text |Cite
|
Sign up to set email alerts
|

Helping patients with localized prostate carcinoma manage uncertainty and treatment side effects

Abstract: BACKGROUNDThe objective of this study was to test the efficacy of an individualized uncertainty management intervention delivered by telephone to Caucasian and African‐American men with localized prostate carcinoma and directed at managing the uncertainties of their disease and treatment.METHODSThe authors delivered a psychoeducational intervention by phone to men with prostate carcinoma, with or without supplemented delivery to a close family member, that was directed at managing uncertainty and improving sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
310
1
18

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(336 citation statements)
references
References 76 publications
7
310
1
18
Order By: Relevance
“…RC led to the greatest improvements in interpersonal outcomes for couples, and had some of the strongest effect sizes overall, which suggests that this may be an important area of need for couples living with chronic illness. Another key observation was that many couples interventions achieved greater effects than the same or similar patient-only intervention across emotional [42], interpersonal [37,43,44], cognitive [41,49], and somatic outcomes [46,48]. This suggests that partner-inclusion may provide benefits beyond that of the content of the intervention itself.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RC led to the greatest improvements in interpersonal outcomes for couples, and had some of the strongest effect sizes overall, which suggests that this may be an important area of need for couples living with chronic illness. Another key observation was that many couples interventions achieved greater effects than the same or similar patient-only intervention across emotional [42], interpersonal [37,43,44], cognitive [41,49], and somatic outcomes [46,48]. This suggests that partner-inclusion may provide benefits beyond that of the content of the intervention itself.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies compared the couples intervention with a patient-only intervention [35,36,37,38,39,40], eight studies used a patient-only comparison group and a usual care control group [41,42,43,44,45,46,47,48], one study compared two types of couples interventions with a patient-alone comparison group [49], and the remaining twenty compared a couples intervention with usual care or waiting-list controls. Twenty-eight studies reported effect sizes, or provided information to calculate effect sizes.…”
Section: Main Descriptivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mishel et al conducted two related RCTs assessing symptom management in both AA and white men, focused on improving selfefficacy for symptom management in men receiving treatment for localized PCa using a DVD/booklet/telephone intervention. 37,38 Telephone/Videotape/DVD Interventions (n=2). The effect of an "uncertainty management" invention on symptom control, using weekly telephone conversations with nurses for 8 weeks, was assessed at baseline, 3 months, and 7 months.…”
Section: Interventions To Improve Outcomes For Prostate Cancer Survivorsmentioning
confidence: 99%